Betacellulin regulates peripheral nerve regeneration by affecting Schwann cell migration and axon elongation - Yaxian Wang; Fuchao Zhang; Yunsong Zhang; Qi Shan; Wei Liu; Fengyuan Zhang; Feiyu Zhang; Sheng Yi (BMC, 2021)
Abstract Background Growth factors execute essential biological functions and affect various physiological and pathological processes, including peripheral nerve repair and regeneration. Our previous sequencing data showed that the mRNA coding for betacellulin (Btc), an epidermal growth factor protein family member, was up-regulated in rat sciatic nerve segment after nerve injury, implying the potential involvement of Btc during peripheral nerve regeneration. Methods Expression of Btc was examined in Schwann cells by immunostaining. The function of Btc in regulating Schwann cells was investigated by transfecting cultured cells with siRNA segment against Btc or treating cells with Btc recombinant protein. The influence of Schwann cell-secreted Btc on neurons was determined using a co-culture assay. The in vivo effects of Btc on Schwann cell migration and axon elongation after rat sciatic nerve injury were further evaluated. Results Immunostaining images and ELISA outcomes indicated that Btc was present in and secreted by Schwann cells. Transwell migration and wound healing observations showed that transfection with siRNA against Btc impeded Schwann cell migration while application of exogenous Btc advanced Schwann cell migration. Besides the regulating effect on Schwann cell phenotype, Btc secreted by Schwann cells influenced neuron behavior and increased neurite length. In vivo evidence supported the promoting role of Btc in nerve regeneration after both rat sciatic nerve crush injury and transection injury. Conclusion Our findings demonstrate the essential roles of Btc on Schwann cell migration and axon elongation and imply the potential application of Btc as a regenerative strategy for treating peripheral nerve injury.